1990
DOI: 10.1002/chin.199023199
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Studies on Antidiabetic Agents. Synthesis and Hypoglycemic Activity of 5‐(4‐(Pyridylalkoxy)benzyl)‐2,4‐thiazolidinediones.

Abstract: The pyridylethanols (I) are transformed into the p‐nitrophenyl ethers (III) which undergo coupling with the acrylate (IV) via reduction and diazotization to form the pyridylethoxyphenylpropionates (V).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 0 publications
0
51
0
1
Order By: Relevance
“…All of the TZDs were synthesized at Nippon Chemiphar (Misato, Japan). Troglitazone, pioglitazone-HCl (pioglitazone), and BRL-49653 were synthesized as previously described (20)(21)(22). NC-2100 {[±]-5-[(7-benzyloxy-3-quinolyl)methyl]-2,4-thiazolidinedione} was synthesized using methods described in Patent Cooperation Treaty patent WO-9612719.…”
Section: Methodsmentioning
confidence: 99%
“…All of the TZDs were synthesized at Nippon Chemiphar (Misato, Japan). Troglitazone, pioglitazone-HCl (pioglitazone), and BRL-49653 were synthesized as previously described (20)(21)(22). NC-2100 {[±]-5-[(7-benzyloxy-3-quinolyl)methyl]-2,4-thiazolidinedione} was synthesized using methods described in Patent Cooperation Treaty patent WO-9612719.…”
Section: Methodsmentioning
confidence: 99%
“…This compound is a selective PPARγ agonist and weak PPARα agonist which improves hyperlipidemia and hyperglycemia in obese and diabetic animals. [9][10][11] It has also been shown to inhibit the growth of human hepatocellular carcinomas, and esophageal squamous, gastric and pancreatic cancer cells in vitro. [12][13][14][15] In addition, pioglitazone and another PPARγ agonist, troglitazone, are reported to suppress formation of dextran sodium sulfate (DSS)/ azoxymethane (AOM)-induced aberrant crypt foci (ACF) in the rat colon.…”
mentioning
confidence: 99%
“…Thus, condensation of 3 with o-phenylenediamine (13) and 4-(chlorophenyl)-1,6-diamino-2-oxo-1,2-dihydropyridine-3,5-dicarbonitrile (14) 23 3 , H enone and H-5 thiadiazepine , respectively. The reaction of 3 with 1,4-binucleophiles proceeds via γ-pyrone ring opening followed by an intramolecular condensation reaction to effect cyclization leading to seven membered ring systems.…”
Section: Resultsmentioning
confidence: 99%
“…2 2,4-TZDs differ markedly from other antidiabetic drugs in that they are effective in normalizing glucose and lipid metabolism associated with insulin resistance and therefore are expected to be useful in treatment of type 2 diabetes mellitus and obesity. [3][4][5] Besides, it was reported that some 2,4-TZDs have been used as antihyperglycemic 6 and aldose reductase (AR) inhibitory agents with dual activity. 7 There is a great interest in 2,4-TZD derivatives as aldose reductase inhibitors (ARIs), 7,8 since they can be viewed as hydantoin bioisosters potentially free of the hypersensitivity reactions which are linked to the presence of the hydantoin system.…”
Section: Introductionmentioning
confidence: 99%